PROTECTING LOCAL STARTUPS: REFORMULATING FOREIGN INVESTMENT POLICIES FOR INDONESIA’S SUSTAINABLE ECONOMY - Rihardi, Satrio Ageng (Doctoral of Law Program, Faculty of Law, Universitas Diponegoro, 2025)
Economic growth in a country is largely influenced by investment levels, both from domestic and foreign sources. In Indonesia, foreign investment plays a crucial role in driving business expansion. However, it often overlooks the interests of local businesses, especially startups. This study aims to analyze the need for reformulating legal policies regarding foreign investment to protect local startups in Indonesia. By adopting a doctrinal legal research approach, this study investigates existing laws and regulations, identifying legal challenges arising from the influx of foreign investors into the startup sector. The findings of the study highlight that while foreign investment significantly contributes to the country’s economic development, its presence without adequate regulation can negatively affect local startups. Many local companies struggle to compete with foreign entities, which may have more financial resources and market power. Therefore, it is essential for the government to strengthen policies regarding foreign ownership in local startups and offer legal protections for domestic businesses. Restrictions on foreign investment in this sector are necessary to prevent foreign domination that could harm local enterprises and ensure a healthy, competitive market environment. Reformulating foreign investment policies is also vital to foster the growth of domestic industries, create job opportunities, and reduce dependency on imported products. These changes would not only benefit local startups but also promote a more sustainable and balanced economic growth for Indonesia. In conclusion, clearer and more decisive legal frameworks surrounding foreign investment are crucial to safeguard the interests of local companies, ensuring that Indonesia’s economy remains competitive and continues to grow in the long term.